The Damage of Hepar Cells of White Male Mice (Rattus norvegicus) which are induced by Carbon Tetrachloride (CCl4) after being given Bawang Dayak (Eleutherine palmifolia Merr.) Ethanol Extract - Aulia Risqi Rohmatin; Eko Susetyarini; Samsun Hadi (Universitas Sebelas Maret, 2015)
The purpose of this study is to determine the effect of giving Bawang Dayak extract as a hepatoprotector to CCl4 induced mice. The research design used in this study was experimental research design by using 25 white male mice aged 2-3 months as samples. The ethanol extract of Bawang Dayak was given orally and induce by using intraperitoreal injection, so the treatment was divided into 5 groups; group 1) negative control (without treatment), 2) positive control which was induced CCl4 at a dose 1.3 ml/kg BW ip, 3) given Bawang Dayak extract at a dose 90 mg/kg BW po + CCl4 induced at a dose 1.3 ml/kg BW ip, 4) given Bawang Dayak extract at a dose 100 mg/kg BW po + CCl4 induced at a dose 1.3 ml/kg BW ip, 5) given Bawang Dayak extract at a dose 110 mg/kg BW po + CCl4 induced at a dose 1.3 ml/kg BW ip. The treatment was done for 53 days. On the 54th-57th day, the mice were injected CCl4 intra peritoneal. On the 58th day, the mice were dissected and taken the hepar organ. After that, making the hepar preparat with safranin staining was done. The observation was done by looking at the damaged hepar cells which were classified into piknotik, main karioreksi and kariolisis from 3 fields of view. The data was analyzed by Anova One Way. The result of the study showed the average score of hepar damage of group 1=48, group 2=107.4, group 3=89.2, group 4=61.8, and group 5=45. The analysis showed that giving Bawang Dayak extract at a dose 110 mg/kg BW could improve hepatoprotector CCl4 induced mice. Keywords: Bawang dayak, CCl4, damage histology liver cells.